Added value of contrast-enhanced and diffusion-weighted MRI data sets for characterization of perianal fistulas; single center experience (Annals of Medical Research, 2021)
Aim: Our aim in this study is to determine the effectiveness of fat-suppressed T2-weighted (FS-T2W), FS-T2W+Diffusion-weighted image (DWI) and FS-T2W+Contrast-enhanced (CE) magnetic resonance imaging (MRI) data sets in the diagnosis of perianal fistula (PAF).Material and Methods: Retrospective analysis of 207 patients with a history of PAF operation between January 2018 and March 2020 was performed. The inclusion criteria were patients with PAF who underwent MRI prior to surgery and had a detailed intraoperative report. MRI data sets were evaluated by a radiologist, assessed fistula type, internal/external orifice position and presence of abscess/secondary tracts. The Cohen’s kappa (κ) statistic was used to define the level of between from intraoperative findings and MRI data sets agreement. The sensitivity and specificity were compared using the McNemar’s test.Results: All MRI data sets showed the presence of PAF correctly (n = 67, 100%). When the type of PAF per St James and AGA classification, presence of perianal abscesses/secondary tract agreement between intraoperative findings and MRI data sets is evaluated; moderate agreement for isolated FS-T2W data set, almost perfect agreement for combined FS-T2W+DWI and FS-T2W+CE data sets. In the evaluation of agreement for internal/external orifice position; substantial agreement for isolated FS-T2W data set, almost perfect agreement for combined FS-T2W+DWI and FS-T2W+CE data sets. Combined FS-T2W+DWI and FS-T2W+CE data sets have equal sensitivity and specificity each other (p = 0.544) and both data sets higher sensitivity and specificity than isolated FS-T2W data set (p 0.001, p 0.001, respectively).Conclusion: Adding DWI or CE data sets to the FS-T2W data set in the diagnosis of PAF has been shown to detect both diagnosis and complications with high accuracy. Combined FS-T2W+DWI and FS-T2W+CE data sets have equal sensitivity and specificity, and the use of the FS-T2W+DWI data set can prevent unnecessary use of contrast agent.